The application of mental mapping technique in identifying the legible elements within historical district of Kuala Lumpur City Centre - Tan, Lai Kum; Ujang, Norsidah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Mental mapping technique has been used by Lynch (1960) in his study on the legibility of several American cities. However, there is no confirmation of the applicability of the mental mapping technique in studying the legibility of Malaysian cities. This paper discusses the applicability of this technique in identifying the legible elements of the historical district of Kuala Lumpur city centre. In a pilot study, 15 respondents were asked to sketch maps and images they recognise within the study area. Results indicate that landmark, nodes, district, path and edges are legible elements for historical district of Kuala Lumpur city centre. This is consistent with Lynch’s identification of legible elements. It is found that the mental mapping is a reliable technique to record evidence of people’s cognition of the area however respondents find it difficult to interpret the information or their knowledge about the district into drawings. The technique can be improved by restructuring the questions and providing guidelines of the context such as the boundaries and elements that are located surrounding the district